Effect of angiotensin receptor neprilysin inhibitor in patients of heart failure with reduced ejection fraction with reduced ejection fraction with cardiorenal syndrome type-1 - Molla, M. A.; Kumar, Ashutosh; Goru, Bhawani; Isharat, Sumaiya (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Heart failure is recognized as one of the most common indications for hospitalization. The dysfunction of either the heart or the kidneys affect the functioning of each other and thus play an important role in the quality of life. Methods: This study is a Prospective interventional Cohort study over a period of 18 months in 125 patients. The patients were divided into two broad treatment groups. The primary end point of the study was to quantify the response of ARNI for renal recovery in patients of cardio-renal syndrome and improvement in cardiovascular parameters by measuring the change in urine output, estimated glomerular filtration rate, serum creatinine, change in weight of the patients, control of blood pressure and change in left ventricular ejection fraction. The secondary end-points were evaluated during the 60 days follow up period post admissions. Results: Cardio-renal syndrome was seen in 39% of the patients. On screening e-GFR was 91±14 and 49±8 for group 1and 2 respectively, the median age, UACR was 59 years ,1.0 mg/mmol respectively for both the groups and 19% had micro albuminuria. ACEIs had more reports of hyperkalemia (8/32, 25%), and greater deterioration of renal parameters (10/32, 34%) needing discontinuation of the drug in some patients. Patients also developed cough (6/32, 20%) needing replacement with ARBs. ARNI group developed more hypotension (6/31, 20%). In all cardiovascular and renal end points except UACR, ARNI showed better recovery profile in CRS-1patients including diabetics. Conclusions: This study showed beneficial effects of ARNI in heart failure patients with cardio-renal syndrome.